Injury vulnerability in Spain. Examination of risk among migrant and native workers - Ronda-Perez, E.; Gosslin, A.; Martínez, J.; Reid, Alison (Elsevier BV, 2019)
© 2019 The search for work is one of the largest drivers of migration. Globally there are an estimated 244 million migrants. It is known that occupational accidents are higher in migrant compared with native-born workers; however, there is a lack of information about the reason for these differences. The aim of this study was to use the vulnerability index to identify whether migrant workers were more vulnerable to occupational health and safety risks than native-born workers among a cohort of 306 workers in Spain. Data come from the Spanish Platform of Longitudinal Studies on Immigrant Families (PELFI). For this analysis, we selected current workers with at least one year of work experience in Spain, 18–65 years of age and born in Colombia, Ecuador (n = 217) and a control sample of Spanish-born workers (n = 89). The occupational health and safety vulnerability tool was used. Prevalence and adjusted (by sociodemographic and occupational variables) Odds Ratio (aOR) was calculated to compare migrants with Spanish-born. Latin American workers had a significantly greater prevalence of exposure to occupational hazards (81% than Spanish-born 54%) and to inadequate policies and procedures (38,7% and 22,5% respectively). After adjusting for a range of demographic and occupation-related covariates, the risk of exposure to an overall vulnerability was increased among Latin American workers (aOR: 1,9 (0,9–4,0). Latin American workers were more likely to suffer work-related vulnerability and that may place them at higher risk of work related health problems.